Anticipatory strategies of team-handball goalkeepers - Gutierrez-Davila, M.; Rojas, F. J.; Ortega, M.; Campos, J.; Parraga, J. (Journal of Sports Sciences, 2011)
This study seeks to discover whether handball goalkeepers employ a general anticipatory strategy when facing long distance throws and the effect of uncertainty on these strategies. Seven goalkeepers and four throwers took part. We used a force platform to analyse the goalkeeper's movements on the basis of reaction forces and two video cameras synchronised at 500 Hz to film the throw using 3D video techniques. The goalkeepers initiated their movement towards the side of the throw 193 ± 67 ms before the release of the ball and when the uncertainty was reduced the time increased to 349 ± 71 ms. The kinematics analysis of their centre of mass indicated that there was an anticipatory strategy of movement with certain modifications when there was greater uncertainty. All the average scores referring to velocity and lateral movement of the goalkeeper's centre of mass are significantly greater than those recorded for the experimental situation with bigger uncertainty. The methodology used has enabled us to tackle the study of anticipation from an analysis of the movement used by goalkeepers to save the ball.